ENT 530 Social Media Portfolio: Tauhu Bergedil Gebu / Ainaa Mohd Yasir - Mohd Yasir, Ainaa (2021)
Tauhu Bergedil Gebu is a company that sells tauhu bergedil , a tofu stuffed with mashed potato and minced beef or chicken which is eaten with sambal kicap . It is a rising snack which was recently popular in Malaysia. The demand for tauhu bergedil keeps on increasing every day. Given the opportunity, Tauhu Bergedil Gebu was set up to satisfy the increasing demands for tauhu bergedil. Our target market for this business focuses more on people who have a busy daily routine. Next target market would be those who love to eat spicy food and those who like experiencing new food. This snack can make one full with just one meal, experiencing a new taste of food and satisfying those who favor fire. Tauhu Bergedil Gebu was established since November 2020 at Ampang, Kuala Lumpur. We strive to sell a delicious tauhu bergedil that would make one crave for more at an affordable price only. We started to promote the business on Facebook to make it known to the public. The facebook page contains teasers, updates and feedback on the food product. We hope that this company will keep expanding and continue to serve people with delicious food in the future.